If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 284 + -2x = 43x + 19 Reorder the terms: 284 + -2x = 19 + 43x Solving 284 + -2x = 19 + 43x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43x' to each side of the equation. 284 + -2x + -43x = 19 + 43x + -43x Combine like terms: -2x + -43x = -45x 284 + -45x = 19 + 43x + -43x Combine like terms: 43x + -43x = 0 284 + -45x = 19 + 0 284 + -45x = 19 Add '-284' to each side of the equation. 284 + -284 + -45x = 19 + -284 Combine like terms: 284 + -284 = 0 0 + -45x = 19 + -284 -45x = 19 + -284 Combine like terms: 19 + -284 = -265 -45x = -265 Divide each side by '-45'. x = 5.888888889 Simplifying x = 5.888888889
| -2(y-4)=12-y | | 25x^2-49=0 | | c^2=25 | | 5xn-3=32 | | 5(y+2)+3y=50 | | 3t+8t+3t+3t= | | 11-9x=87-37x | | -2w+5=26+w | | 8x=64 | | -5(x+37)= | | 15x^3+44x^2+11x-6=0 | | 6(x-5)=5(x+5) | | -90-9x=9x+18 | | -2x^2+128=0 | | 4x^2=26x-30 | | 11x-(6x+6)=19 | | 2x+14=-41-9x | | 7b+5b= | | 2(y-12)+2y=-84 | | -20(-31)= | | -2[y-4]=12-y | | 5(3x-4)=2(5x+20) | | 3b=45 | | 100-4x=2x+22 | | 5+x=7 | | x+8x+9x= | | 2L*2-3=12 | | 4y-3(y+8)=12 | | -4x^2+16=0 | | 26=x-12 | | (9x-1)(2x+9)=0 | | 3x+1=6x+10 |